The Principal's Example in Developing Students' Responsible Character - Sopian Ansori; Parhan (Universitas Islam Negeri Walisongo, 2026)
This study aims to determine the role of the principal's exemplary behavior in fostering a character of responsibility in students at Muhammadiyah Masbagik High School. Leadership in education is one of the key factors in achieving educational goals, especially in developing student character. The role of the principal is very important in fostering a character of responsibility in students, because character education cannot be separated from the leadership of the principal. This study uses a qualitative approach, a case study type with data collection procedures, namely observation, interviews, and documentation. While the data analysis technique uses the Milles and Hubberman data analysis model, namely: (1) Data Reduction, (2) Data Presentation, (3) Data Verification to test the validity of data obtained from the field using several techniques of extended participation, persistent observation, and triangulation. The results of the study show that the principal's exemplary leadership in fostering a character of responsibility in students: 1 the principal shows good behavior in front of students, 2 respects teachers and staff, 3 appreciates students and 4 inspires students. Theoretically, this research serves as a reference for principal leadership in developing students' responsible character. Practically, this research serves as a guideline and reference for implementing principal leadership in realizing students' responsible character in schools.